Assessing the adoption of biosecurity measures among extensive livestock producers: a case study in the free-range pig sector of Corsica - Theo Loeillot; Marie Gisclard; Bastien Trabucco; François Charrier; Ferran Jori; Nicolas Antoine-Moussiaux; Alexis Delabouglise (BMC Veterinary Research, 2025)
Abstract Background Increasingly exposed to emerging sanitary risks, extensive livestock farming systems are confronted with the imperative of incorporating biosecurity measures in their production models in order to limit the risk of introduction and diffusion of animal pathogens. Yet, ex-ante assessment methods of the likelihood of biosecurity measures implementation are poorly documented. Our study aimed at comparing alternative methods of elicitation of preferences to assess the attitude of extensive livestock farmers towards biosecurity measures. We used, as a case study, the Regional Porcine Sanitary Plan (RPSP) elaborated for the free-range pig sector of Corsica Island to meet the newly established national disease prevention requirements of France in the face of risk of African Swine Fever introduction. Methods The RPSP imposed (1) a fencing of the breeding pigs’ area, (2) the neutering of the pigs not used for breeding, and (3) a management process of dead pigs’ carcasses found on pastures. We evaluated four attributes of the sanitary plan, including (1) proportion of the implementation cost covered by state subsidies, (2) mandatory carcass management, (3) people allowed to neuter gilts, (4) the age limit for neutering. We performed interviews of a sample of free-range pig farmers using three methods in parallel, namely (1) direct qualitative elicitation, (2) attributed-based stated choices and (3) semi-quantitative ranking of attributes. Results Farmers’ preference for a high subsidization of the sanitary plan and for enforcing the neutering of pigs at an early age was consistent across all used methods. Participants expressed heterogeneous preferences for the two other attributes. Half of the respondents were reluctant to entrust veterinarians with neutering gilts while the other half deemed veterinarians’ intervention compulsory. Contradictory preferences were obtained on rendering carcass management mandatory depending on the elicitation method. Conclusion Our study demonstrates the added value of using choice-based methods, where respondents weigh the individual costs and benefits associated with different options, in combination with qualitative or semi-quantitative ranking methods in which farmers express their opinions and give more consideration to their community interest. It also reveals potential issues of heterogeneities among farmers’ preferences that need to be taken into consideration in similar surveys.